Students’ errors in solving climate change context mathematical modeling problems - Mursyidah J Parandrengi; Cecil Hiltrimartin (Jurnal Elemen, 2023)
This research is a descriptive study that aims to describe the errors of students of the Faculty of Education and Teacher Training (FKIP), Sriwijaya University, in solving Climate Change context mathematical modeling problems, to minimize errors made in solving mathematical modeling problems, especially in the context of climate change in the future. No one has researched student errors in solving mathematical modeling problems in the Climate Change context using the Newman error procedure. Data collection techniques used in this study included tests and semi-structured interviews. The data analysis technique used for test data is by analyzing errors using the Newman procedure. The results of this study with 52 participants were types of errors by FKIP Sriwijaya University in solving Climate Change context mathematical modeling problems as follows for question 1 and question 2, and respectively there were 23.1% and 15.4% errors in understanding the problem, 46.2% and 96.2% transformation errors, 32.7% and 96.2% writing. The causes of errors are errors in reading, errors in determining the problem and existing information, errors in making assumptions, errors in identifying variables, and errors in making mathematical models.